Islamic Educational Values in Lombok’s Ancient Tomb Architecture: A Local Islam Perspective on the Batu Layar, Loang Baloq, and Selaparang Tombs - Husnul Haetami; Jamaluddin Jamaluddin; Baharudin Baharudin (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study examines the Islamic educational values embedded in the architecture of ancient tombs in Lombok from the perspective of local Islam, focusing on the Batu Layar, Loang Baloq, and Selaparang tomb sites. The research aims to explore how architectural elements and religious traditions associated with these tombs reflect Islamic teachings and contribute to the preservation of local Islamic culture among the Sasak community. This study employs a qualitative library research approach by analyzing academic literature, historical records, cultural studies, and relevant scholarly publications concerning Lombok’s Islamic heritage and sacred architecture. Data were analyzed descriptively and interpretively to identify educational, religious, and cultural values represented in the tomb architecture and related pilgrimage practices. The findings reveal that the architecture of the ancient tombs embodies various Islamic educational values, including faith (aqīdah), devotion (‘ibādah), respect for righteous figures, social solidarity, and cultural preservation. Architectural features such as tomb orientation toward the qibla, protective structures (cungkup), and the use of local materials demonstrate the integration of Islamic principles with Sasak cultural traditions. Furthermore, pilgrimage practices (roah makang) conducted at these sites function as informal educational media that transmit religious knowledge, moral teachings, collective memory, and communal identity across generations. The study concludes that the ancient tombs of Lombok serve not only as historical and religious heritage sites but also as educational spaces where Islamic values are continuously interpreted and practiced within the framework of local culture. This research contributes to the discourse on local Islam and Islamic educational heritage in Indonesia.